ANIMATION BASED INTRODUCTION VIDEOS MOTION GRAPHIC KADIN NORTH SUMATRA - Pandi Barita Nauli Simangunsong (INFOKUM, 2022)
Animation is a moving image in the form of a set of objects (images) arranged in an orderly manner following a predetermined flow of movement at each additional count of time that occurs. The image can be in the form of images of living things, inanimate objects, or writing. The North Sumatran Chamber of Commerce and Industry (Kadin) desperately needs an attractive promotional media, so that people know and know about the North Sumatran Chamber of Commerce and Industry (Kadin). In the process of making animation, a story idea, scenario, and storyboard are needed. This animation provides and explains what the North Sumatran Chamber of Commerce and Industry (Kadin) is and explains the history of the North Sumatran Chamber of Commerce and Industry (Kadin). The process of making this animation uses Adobe After Effects CS6 and Adobe Illustrator CS6 software so that making this animation more interesting and understandable by the public. The North Sumatra Chamber of Commerce and Industry (Kadin) is a company engaged in services and industry, therefore this introduction animation is needed by the North Sumatran Chamber of Commerce and Industry (Kadin) in order to become a company that continues to grow and is well known throughout the world. Animation is a moving image in the form of a set of objects (images) arranged in an orderly manner following a predetermined flow of movement at each additional count of time that occurs. The image can be in the form of images of living things, inanimate objects, or writing. The North Sumatran Chamber of Commerce and Industry (Kadin) desperately needs an attractive promotional media, so that people know and know about the North Sumatran Chamber of Commerce and Industry (Kadin). In the process of making animation, a story idea, scenario, and storyboard are needed. This animation provides and explains what the North Sumatran Chamber of Commerce and Industry (Kadin) is and explains the history of the North Sumatran Chamber of Commerce and Industry (Kadin). The process of making this animation uses Adobe After Effects CS6 and Adobe Illustrator CS6 software so that making this animation more interesting and understandable by the public. The North Sumatra Chamber of Commerce and Industry (Kadin) is a company engaged in services and industry.